COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN WISATA BUDAYA BERKELANJUTAN BERBASIS MASYARAKAT STUDI PADA SITUS CIUNG WANARA DI KABUPATEN CIAMIS - Asep Nurwanda; Elis Badriah (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2026)
The development of sustainable cultural tourism is a strategy to enhance a region's economic, social, and cultural value while preserving local cultural heritage. Ciamis Regency possesses significant cultural tourism potential, notably the Ciung Wanara Site, which embodies historical, cultural, and local wisdom values. However, developing this potential faces various challenges, including limited coordination among stakeholders, suboptimal community participation, limited management capacity, and a lack of integration between cultural preservation and tourism development. These conditions highlight the importance of a collaborative governance approach that brings together the government, the public, cultural communities, business actors, academics, and other stakeholders in joint decision-making and tourism management processes. This study aims to analyze the implementation of collaborative governance in community-based sustainable cultural tourism development in Ciamis Regency and to identify the dynamics, roles of actors, supporting and inhibiting factors, and strategies for strengthening collaboration in managing cultural tourism destinations. The study employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, documentation, and literature review, and subsequently analyzed interactively through data reduction, data presentation, and conclusion drawing. The analysis focuses on dialogue and participation processes, trust-building, facilitative leadership, resource sharing, collective action capacity, and collaborative outcomes. The study's novelty lies in developing a collaborative governance perspective that integrates community empowerment, cultural heritage preservation, and destination sustainability within a single cultural tourism management framework for Ciamis Regency. The study is expected to yield recommendations for an inclusive, participatory, and sustainable collaboration model to serve as a basis for strengthening cultural tourism development policies in Ciamis Regency.